Harnessing Big Data for Targeted Marketing: Opportunities and Challenges for Retailers in a Post-Pandemic World - Ikhsan Nendi (Journal of Strategic Marketing and Applied Economics, 2025)
The COVID-19 pandemic has accelerated the adoption of digital technologies across sectors, including retail, where the use of big data has become increasingly important to understand consumer behavior and facilitate targeted marketing. In this context, this study aims to analyze the opportunities and challenges retailers face in leveraging big data to improve their marketing effectiveness in a post-pandemic world. The method used in this study is a qualitative approach through in-depth interviews with industry leaders and case study analysis of companies that have successfully implemented big data strategies. The results show that the utilization of big data provides retailers with valuable insights into consumer preferences, allowing them to create more personalized and relevant marketing campaigns. However, the study also identified significant challenges, including data privacy concerns, complexity in system integration, and the need to develop analytical skills among the workforce. These findings provide important insights for retailers in formulating more responsive and adaptive marketing strategies, as well as addressing the challenges that arise from the use of big data. This research is expected to contribute to the literature on digital marketing and provide practical guidance for practitioners in the retail industry.